Packaging: The antecedents of purchase intention and behaviour when comparing generations Y and Z - Dias, Pedro Ribeiro Novais (2022)
Brands are increasingly concerned with sustainable and environmentally friendly packaging. In addition, the younger generations, which is an important target are increasingly aware of sustainable issues. This study aims to identify the relations between the environmental knowledge and environmental concern with green purchase intention and green purchase behaviour in the generations Y and Z in Portugal. Specifically, this study aimed to identify any moderating effect of the generations in these relations regarding bottled water with sustainable packaging. To achieve this aim, a quantitative research was conducted surveying a sample of 173 Portuguese between generation Y and Z (88 and 85 people respectively). Data was further analysed through factorial analysis and regression modelling. The results showed that environmental knowledge and environmental concern influences green purchase intention, and the latter also influences green purchase behaviour. However, generation is not shown to be a moderating factor in any of the above relationships.